THE ROLE OF INTERCULTURAL SIMULATION GAMES IN THE STUDY PROCESS: THE IMPACT ON THE DEVELOPMENT OF INTERCULTURAL COMPETENCE - Gerulaitienė, Eglė (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Intercultural simulation games are defined as instructional activities that engage and challenge participants with certain experiences. The use of intercultural simulation games in the study process while developing intercultural competence becomes very essential part of education. The primary prerequisite for development of intercultural competence is multicultural environment and methods aimed at creation or simulation of real-life activity and situation. This article examines the conceptual bases for intercultural simulation games in the study process and its impact or efficacy on the development of intercultural competence. Intercultural simulation games are designed and conducted to develop skills and inoculate participants for future experience in a different or unknown cultural environment.